Strategy for Transferring Civil Servants to the Capital City of Nusantara - Wijanarko, Ugeng (International Journal of Social Service and Research, 2026)
This policy paper analyzes the strategy for relocating Indonesian Civil Servants (ASN) to the National Capital City of Nusantara (IKN) within the context of early-stage development and public policy dynamics. Although significant progress has been achieved in building core infrastructure within the Central Government Core Area (KIPP), the relocation process remains suboptimal due to regulatory uncertainty, incomplete supporting infrastructure, the absence of additional incentives, and limited individual and family readiness among civil servants. The study applies Root Cause Analysis (RCA) to identify fundamental challenges and utilizes the USG (Urgency, Seriousness, Growth) framework to prioritize policy issues. Furthermore, a grid analysis based on effectiveness, efficiency, and appropriateness criteria is conducted to determine the most strategic policy alternative. The findings indicate that the provision of integrated transportation infrastructure ranks as the top priority, obtaining the highest evaluation score and functioning as a catalyst for optimizing residential, office, social, and economic ecosystems. Reliable transportation not only accelerates asset utilization but also enhances quality of life and strengthens public confidence in the sustainability of IKN development. Therefore, accelerating ASN relocation requires a holistic strategy that integrates infrastructure readiness, regulatory certainty, and adaptive change management oriented toward family well-being.